DIGITAL REFORM IN LEGAL COMPLAINT DRAFTING: CONSTRUCTION OF AN AI-BASED PLANNING SYSTEM TO REDUCE THE RISK OF OBSCURE LIBEL - Bunda, Ridho Harapan; Aida, Welven; Utami, Urfi (Awang Long Law Review, 2025)
Digitalization in legal practice is becoming increasingly essential, especially in the drafting of legal claims, which demands high accuracy and certainty. Errors in drafting can result in obscuur libel rulings, potentially obstructing the litigation process. To address this, innovation is needed to enhance the accuracy and effectiveness of legal document preparation. The use of Artificial Intelligence (AI) is expected to significantly improve this process by helping legal practitioners produce more precise documents and reduce legal uncertainty. This research aims to design an AI-based system that is both technically precise and legally compliant, enhancing the clarity of claim substance. The objective is to reduce the risk of obscuur libel rulings, promote adaptive and accountable court digitalization, and optimize the drafting process. This study employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). It begins with a needs analysis to identify the issues faced by legal practitioners, followed by the development of a system using Natural Language Processing (NLP) techniques to automate legal document preparation. The system is designed to help practitioners draft legal claims more accurately and efficiently. The results show that the AI-based system reduces drafting time by up to 70% compared to manual methods. The system also consistently detects ambiguous sentences and legal errors. Feedback from legal practitioners confirms that the user interface is intuitive and accessible, even for those without technical backgrounds. The automated feedback and recommendations based on NLP enhance the clarity and precision of legal documents. In conclusion, the system demonstrates great potential in improving the efficiency and accuracy of legal claim drafting, contributing significantly to the digitalization of the legal field.